Case Report: Plasmacytoma of External Urethral Meatus - Su, Wen; Zeng, Liang; Zhao, Dongsheng; Fu, Ying; Tang, Jin (Frontiers in Endocrinology, 2022)
Abstract Rationale: Extramedullary plasmacytoma (EMP) can occur in various parts of the body. It is generally accepted that the highest site of occurrence is the head and neck region (80% to 90%), followed by the gastrointestinal tract and the skin. It is worth mentioning that the site of disease, in this case, was the urethral meatus, which is extremely rare in clinical practice. Patient concerns: A 50-year-old female complained of an episode of painless gross hematuria without symptoms of frequent urination, urgency, abdominal pain, abdominal distension, fever, or oliguria. The patient has no history of smoking or drinking and denied any family history of solid malignancy or hematological disease. Diagnosis and interventions: Urethrocystoscopy revealed urethral polypoid hyperplasia, which we initially thought could be a urethral caruncle. The patient was asked to undergo caruncle resection after 1 week of potassium permanganate sitz bath, and postoperative pathology revealed plasmacytoma. After that, a whole-body MRI showed no other lesions. She received postoperative radiotherapy. Outcomes: During radiotherapy, the patient's condition and appetite were fair, and the skin mucositis was I°. Pelvic contrast-enhanced MRI and whole-body PET-CT 6 months after urethral meatus lumpectomy and radiotherapy showed changes without obvious abnormal signs. No recurrence or metastasis was detected after one year of follow-up. Lessons: Urinary EMP is a rare disease. It is not easy to diagnose due to its rare site of occurrence and non-specific symptoms. The diagnosis of EMP requires a combination of imaging studies and pathological findings. Currently, surgery combined with radiotherapy or radiotherapy alone is the mainstay treatment and usually results in an acceptable local control rate. At the same time, chemotherapy cannot be ignored.